2016
DOI: 10.3847/0004-637x/831/1/106
|View full text |Cite
|
Sign up to set email alerts
|

Fermi/Lat Study of Gamma-Ray Emission in the Direction of the Monoceros Loop Supernova Remnant

Abstract: We present an analysis of the gamma-ray measurements by the Large Area Telescope onboard the Fermi Gammaray Space Telescope in the region of the supernova remnant(SNR) Monoceros Loop(G205.5+0.5). The brightest gamma-ray peak is spatially correlated with the Rosette Nebula, which is a molecular cloud complex adjacent to the southeast edge of the SNR. After subtraction of this emission by spatial modeling, the gamma-ray emission from the SNR emerges, which is extended and fit by a Gaussian spatial template. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Sizes of the red circles are enlarged to two times with respect to their angular sizes (1 ′ -2 ′ ). The large white circle indicates the best-fit Gaussian spatial model from F ERM I/LAT observations after subtracting the background and the emission from the Rosette Nebula (Katagiri et al 2016), while the two little white circles show the 2FGL sources of J0636.0+0554 and J0637.8+0737 (Nolan et al 2012). • 941)) and width of 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sizes of the red circles are enlarged to two times with respect to their angular sizes (1 ′ -2 ′ ). The large white circle indicates the best-fit Gaussian spatial model from F ERM I/LAT observations after subtracting the background and the emission from the Rosette Nebula (Katagiri et al 2016), while the two little white circles show the 2FGL sources of J0636.0+0554 and J0637.8+0737 (Nolan et al 2012). • 941)) and width of 4.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 2FGL sources of J0636.0+0554 and J0637.8+0737 (Nolan et al 2012) are located close to the molecular gas revealed by our new CO survey (two little circles in Figure 9). Very recently, extended gamma-ray emission from F ERMI/LAT observations was found inside the remnant (see Figures 3 and 4 in Katagiri et al 2016). According to our study, the MC concentration in the velocity intervals of 3-12 km s −1 and 18-23 km s −1 , which is shown to be associated with the remnant, is consistent well with the distribution of the backgroundsubtracted gamma-ray emission.…”
Section: Snr G2055+05 (Monoceros Nebula)mentioning
confidence: 99%
“…HESS J0632+057 is located in a complicated region. Within 3 • of its location, there are several gamma-ray point sources from the preliminary seven-year source list, the Monoceros Loop Supernova Remnant, and the Rosette Nebula, which are both known to be extended gammaray sources (Katagiri et al 2016). Located ∼1 • away from the source of interest, there is PSR J0633+0632, a bright, radio-quiet gamma-ray pulsar discovered in the first six months of Fermi-LAT observations (Abdo et al 2009d).…”
Section: Gating Off the Bright Gamma-ray Pulsar Psr J0633+0632mentioning
confidence: 99%
“…So, from the observational point of view, one must distinguish between "direct" clues to investigate the acceleration processes (e.g., radio observations), and "indirect" ones, i.e., those necessitating a target to be revealed such as molecular clouds for relativistic protons (Abdo et al 2010;Acciari et al 2009;Katsuta et al 2012;Katagiri et al 2016;Tavani et al 2010), or radiation from interstellar dust for electrons.…”
Section: Introductionmentioning
confidence: 99%